Adult‐related haematopoietic stem cell donor experiences and the provision of information and psychosocial support: A systematic literature review. (2nd October 2018) - Zomerdijk, Nienke; Turner, Jane M.; Hill, Geoffrey R.
Abstract: For blood cancer patients, haematopoietic stem cells (HSC) donated by a relative can be lifesaving. However, related donors can face significant physical and psychosocial challenges. As the demand for adult‐related HSC donors is increasing, it is important to review our understanding of adult‐related HSC donors' need for and availability of information and psychosocial support with a view to identifying gaps in the literature. A systematic review of relevant studies (2000–2017) was conducted using five databases with supplementary hand searching. Sixteen studies involving 1, 024 related HSC donors met the following criteria: English or Dutch language, peer‐reviewed, sampled first‐time‐related HSC donors, ≥18 years, haematological malignancies, assessed psychosocial aspects, retrospective or prospective and with or without comparison group. Data were abstracted, and study quality was assessed using the PRISMA criteria. Studies contained limited information on the provision of information and psychosocial support. Most studies addressed pre‐donation information, and none reported providing information or support to donors post‐donation. Additionally, few studies formally assessed unmet needs. Recommendations include improved transparency of reporting for the availability, sources and timing of information and psychosocial support, and the identification of unmet needs to enable the development of educational and psychosocial interventions for this invaluable donor population.